Deferoxamine‐activated hypoxia‐inducible factor‐1 restores cardioprotective effects of sevoflurane postconditioning in diabetic rats. (15th May 2017) - Xie, P.; Yang, L.; Talaiti, A.; Wu, J. J.; Yu, J.; Yu, T.; Wang, H. Y.; Huang, B.; Wu, Q.; Maimaitili, Y.; Wang, J.; Ma, H. P.; et al.
Abstract: Aim: The cardioprotective effects of sevoflurane postconditioning (SpostC) are eliminated under diabetic conditions, and the underlying mechanism for this phenomenon remains unclear. Many studies have demonstrated that the hypoxia‐inducible factor‐1 (HIF‐1) signalling pathway in the myocardium is impaired under diabetic conditions. This study was to investigate whether deferoxamine (DFO)‐induced activation of HIF‐1 signalling pathway can restore the cardioprotective effects of SpostC in diabetic rats. Methods: A model of myocardial ischaemia/reperfusion (I/R) injury was induced via ligation of the left anterior descending artery. SpostC was conducted by administering 1.0 MAC sevoflurane. After inducing the I/R injury, the following parameters were measured: myocardial infarct size, cardiac function, myocardial ultrastructure, mitochondrial respiratory function, respiratory chain enzyme activity, rate of reactive oxygen species (ROS) generation, and protein expression of HIF‐1 α, vascular endothelial growth factor (VEGF), cleaved caspase‐3, Bcl‐2 and Bax. Results: After DFO activated HIF‐1 in the impaired myocardium of diabetic rats, SpostC significantly upregulated the protein expression of HIF‐1 α and its downstream mediator VEGF. This improved myocardial mitochondrial respiratory function and respiratory chain enzyme activity and reduced ROS generation as well as the protein expression of cleaved caspase‐3 and Bax. As a result, myocardial infarct size decreased, and cardiac function and mitochondrial ultrastructure improved. Conclusion: This study demonstrates for the first time that abolishment of the cardioprotective effects of SpostC in diabetic rats is associated with impairment of the HIF‐1 signalling pathway and that DFO can activate HIF‐1 to restore these cardioprotective effects of SpostC in diabetic rats.